1996
DOI: 10.1002/(sici)1097-0142(19960301)77:5<934::aid-cncr20>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor content of prostate carcinoma cells estimated by immunohistochemistry is related to prognosis of patients with stage D2 prostate carcinoma

Abstract: Androgen receptor content measured immunohistochemically is a useful prognostic indicator for patients with Stage D2 prostate carcinoma treated with endocrine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 30 publications
3
40
0
Order By: Relevance
“…Finally, AR has recently been suggested to function as a tumor suppressor in epithelium to suppress prostate tumor invasion and metastasis [39]. Also, several reports have shown that higher AR expression and pretreatment testosterone levels predict better response to endocrine therapy [40][42]. Consequently, combined with our results, higher transactivated AR with shorter CAG repeats might inhibit prostate cancer metastasis and predict a good prognosis on ADT.…”
Section: Discussionsupporting
confidence: 76%
“…Finally, AR has recently been suggested to function as a tumor suppressor in epithelium to suppress prostate tumor invasion and metastasis [39]. Also, several reports have shown that higher AR expression and pretreatment testosterone levels predict better response to endocrine therapy [40][42]. Consequently, combined with our results, higher transactivated AR with shorter CAG repeats might inhibit prostate cancer metastasis and predict a good prognosis on ADT.…”
Section: Discussionsupporting
confidence: 76%
“…This was the first report of an association between nuclear AR content and hormonal response and might underline the “driving” AR transcriptional role. A study of 62 patients with untreated metastatic prostate cancer who received ADT showed that high immunohistochemical (IHC) AR content is a favorable prognostic indicator [8]. In addition, image IHC analysis of prostate cancer AR with a pattern/receptogram-oriented approach could accurately predict response to hormone therapy in patients with advanced stage, while AR heterogeneity was associated with poor prognosis in different studies [911].…”
Section: Potential Biomarkers Of Response To Hormonal Therapy (Tabmentioning
confidence: 99%
“…Studies show that aberrant expression of the AR correlate with decreased differentiation and higher Gleason scores in prostate cancer [24][25][26]. Overexpression of the AR is a relatively common phenomena among AIPC patients with about 30% of prostate tumors that progress to androgen independence following androgen ablation expressing increased AR mRNA and protein [27,28].…”
Section: Androgen Receptor In Prostate Cancermentioning
confidence: 99%